2008
DOI: 10.1002/ana.21316
|View full text |Cite
|
Sign up to set email alerts
|

Varicella‐zoster virus in cerebrospinal fluid at relapses of multiple sclerosis

Abstract: The ultrastructural finding of viral particles identical to VZV, together with the simultaneous presence of large quantities of DNA from VZV in the subarachnoid space, almost restricted to the periods of exacerbation, as well as its steady diminution and eventual disappearance from clinical relapse to clinical remission are surprising and constitute the strongest evidence to support the participation of VZV in the pathogenesis of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 39 publications
5
59
0
1
Order By: Relevance
“…In a previous study we have demonstrated that the Chomczynski RNA extraction, followed by a single-primer isothermal amplification, NGS, and metagenomic data analysis, enables to detect both DNA and RNA sequences (Perlejewski et al 2015). Interestingly, a relationship between VZV infection and demyelinating disorders has been previously suggested by the demonstration of more frequent presence of VZV-DNA and viral proteins in CSF of MS patients as compared to patients with other neurological diseases or healthy controls (Sotelo et al 2008;Mancuso et al 2007). Further, VZV-DNA is more prevalent in CSF and peripheral blood mononuclear cells during MS relapse than in remission (Sotelo et al 2014;Ordonez et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study we have demonstrated that the Chomczynski RNA extraction, followed by a single-primer isothermal amplification, NGS, and metagenomic data analysis, enables to detect both DNA and RNA sequences (Perlejewski et al 2015). Interestingly, a relationship between VZV infection and demyelinating disorders has been previously suggested by the demonstration of more frequent presence of VZV-DNA and viral proteins in CSF of MS patients as compared to patients with other neurological diseases or healthy controls (Sotelo et al 2008;Mancuso et al 2007). Further, VZV-DNA is more prevalent in CSF and peripheral blood mononuclear cells during MS relapse than in remission (Sotelo et al 2014;Ordonez et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Presence of VZV DNA, however, has been reported in blood cells [45] and CSF [46] from relapsing MS patients. Furthermore, Sotelo et al observed electron microscopically abundance of viral particles identical to VZV in the CSF of MS patients during the initial days of disease relapse [47]. However, when Burgoon et al used identical electron microscopic and PCR techniques they failed to identify presence of viral particles or DNA in MS CSF or acute MS plaques [48].…”
Section: Varicella-zoster Virusmentioning
confidence: 99%
“…Varicella is usually benign in children; however, it may also result in complications that might include pneumonia, encephalitis, multiple sclerosis, and death (18,21,24). Primary infection is commonly followed by the establishment of lifelong latent infection of the sensory ganglia, which can be reactivated later in life, resulting in herpes zoster (shingles).…”
mentioning
confidence: 99%